Cardiac troponin I, fructosamine, and cardiovascular parameters in dogs with diabetes mellitus - Soares, Frederico A. C.; Machado, Letícia; Carvalho, Guilherme L.; González, Félix H. D.; Pöppl, Álan G. (Austral Journal of Veterinary Sciences, 2018)
Diabetes mellitus (DM) is a common endocrinopathy in dogs, however, the relationship between canine DM and cardiomyopathy is still unclear. The aims of this study were: to evaluate serum troponin I concentrations in diabetic dogs under treatment with insulin; to evaluate the hypothesis that the time of DM diagnosis could influence the troponin I concentration; and to evaluate the relationship between biochemical and cardiovascular parameters in diabetic dogs. This is a cross-sectional study including diabetic canine patients under NPH insulin treatment. Troponin I concentration, systolic blood pressure (SBP), complete blood count, serum fructosamine concentration, biochemical profile, and Doppler echocardiography assesments were carried out in each patient, as well as in age- and size- matched healthy controls. All diabetic dogs had concentrations of troponin I below the limits of detection of the assay. There was no difference between cardiovascular parameters between diabetic and healthy control dogs. There was no correlation between time of DM diagnosis and cardiovascular parameters. There was a significant positive correlation between SBP and fructosamine in diabetic dogs (r=0.54; P<0.01). Diabetic dogs receiving insulin treatment, regardless of the time of diagnosis, do not have significantly elevated serum troponin I. The results also suggest that fructosamine levels can be associated with high blood pressure, suggesting a possible correlation between fructosamine levels and vascular complications.